Post‐diagnostic dietary changes in prostate cancer: associations with patients' wellbeing and the perceptions of GPs. (24th October 2016) - Kassianos, A. P.; Raats, M. M.; Gage, H.
Abstract : This article aims to investigate associations between perceived control and health‐related quality of life (HRQOL) with dietary changes after prostate cancer diagnosis and to explore General Practitioners' (GPs) perceptions on the role of diet in prostate cancer post‐diagnosis. Ninety‐five prostate cancer patients completed measures of dietary change, one for after diagnosis and another for after therapy. They also scored their HRQOL and perceived control. There were discrepancies in dietary changes reported between a general question (28.4% no dietary changes) and a specific (42.1%–51.5% range of no change for various food items). Most patients initiated healthy changes. Patients who changed their diet after diagnosis had lower cognitive functioning and external locus of control (doctors). Patients who changed their diet after therapy had lower cognitive and emotional functioning, quality of life and external locus of control (doctors). Then, fourty‐four GPs responded to an online survey. Their open‐ended responses were analysed using Content Analysis. They reported interest in the role of diet in cancer but also lack of relevant knowledge. They were skeptical on providing information. Clinical interventions should consider patients' cognitive ability, their relationship with their health professional and their wellbeing. Also, GPs' confidence to provide dietary advice needs to be addressed.